LINGUOCULTURAL FEATURES OF INSERT WORDS IN ENGLISH AND UZBEK LANGUAGES - Nosirova Umidaxon Ikromovna; Maxamadjonova Nodiraxon Axmadiyor qizi (Bright Mind Publishing, 2025)
Language serves not only as a means of communication but also as a mirror reflecting the cultural, social, and psychological characteristics of its speakers. Among the linguistic elements that reveal these connections, insert words — also known as parenthetical words, discourse markers, or pragmatic particles — occupy a significant position. They are used to express the speaker’s attitude, emotions, intentions, and interactional strategies. This article explores the linguocultural features of insert words in English and Uzbek languages, emphasizing their communicative, structural, and cultural functions. By analyzing their pragmatic and semantic roles, this study highlights how such words contribute to maintaining the coherence of discourse and reflecting the cultural identity of speakers. The research also discusses how sociolinguistic and pragmatic norms influence the frequency and choice of insert words in different communicative contexts. Through comparative analysis, the paper aims to expand the understanding of how language structures interact with culture to shape communicative behavior. The findings emphasize the need to consider cultural awareness in translation, language teaching, and cross-cultural communication, since even small lexical items like insert words can carry profound cultural significance and affect mutual understanding between speakers of different languages.
Keywords: linguocultural features, insert words, discourse markers, pragmatic particles, cross-cultural communication, pragmatics, cultural identity.